2014
DOI: 10.1016/j.ygyno.2013.12.040
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of human papillomavirus infection following treatment for cervical neoplasia: A systematic review

Abstract: Objective To systematically review the published literature in order to estimate the incidence and describe the variability of human papillomavirus (HPV) infection in women following treatment for cervical neoplasia. Methods Several scientific literature databases (e.g. PubMed, ISI Web of Science) were searched through January 31, 2012. Eligible articles provided data on (i) baseline HPV infection status within 6 months prior to or at time of treatment (pre-treatment); and (ii) HPV test results for women's f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 49 publications
3
31
0
2
Order By: Relevance
“…It should be noted that estimates of HPV persistence after treatment may represent either truly persistent infections ( i.e ., infections persisting from before treatment), recurrent HPV infections ( i.e ., reinfection after treatment), or newly acquired HPV infections ( i.e ., infections acquired after treatment). In light of our previous systematic review in women post‐treatment, a notable proportion of these “persistent” HPV infections may have been infections acquired after treatment. This is likely of particular concern for studies with long time intervals ( i.e ., 12 and 24 months) between HPV tests in which sexual activity and subsequent HPV exposure are likely to occur.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It should be noted that estimates of HPV persistence after treatment may represent either truly persistent infections ( i.e ., infections persisting from before treatment), recurrent HPV infections ( i.e ., reinfection after treatment), or newly acquired HPV infections ( i.e ., infections acquired after treatment). In light of our previous systematic review in women post‐treatment, a notable proportion of these “persistent” HPV infections may have been infections acquired after treatment. This is likely of particular concern for studies with long time intervals ( i.e ., 12 and 24 months) between HPV tests in which sexual activity and subsequent HPV exposure are likely to occur.…”
Section: Discussionmentioning
confidence: 93%
“…To date, there has been no summary of the literature that examines the estimates of and definitions for HPV persistence after CIN treatment. In 2014, we published a systematic review of HPV incidence after treatment for CIN . In contrast to persistent HPV infections, which are infections that are present at or before treatment and remain present after treatment, incident HPV infections are defined as the detection of a new HPV genotype after treatment for CIN that was not present before or at the time of treatment .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of persistent hrHPV after treatment for cervical dysplasia has been variously reported as 33% at 6 months, 13% at 12 months, and 9.9% at 36 months, depending on the method used to detect HPV DNA and the type of treatment . In the present study population, the frequency of persistent hrHPV infection was 20% at 6 months.…”
Section: Discussionmentioning
confidence: 56%
“…Mounting evidence suggested that HPV infection, especially high-risk (HR)-HPV, was one of the most critical independent risk factors for cervical dysplasia and cervical cancer [3,4]. Since the highest prevalence of HPV infection has been observed in women during their reproductive age [5,6] and pregnancy is considered to be an independent risk factor for HR-HPV infection [7,8].…”
Section: Introductionmentioning
confidence: 99%